VERTICAL SPECIALIZATION IN THE MIDDLE EAST; EVIDENCE FROM THE IMPORT CONTENT OF EXPORTS* - Muhtaseb, Buthaina M.A.; Daoud, Hussam-eldin (European Scientific Journal, ESJ, 2015)
In this study, we provide estimates of vertical specialization (VS), as reflected in the imported content of exports, for four Middle Eastern countries; Jordan, Lebanon, Egypt and Turkey. Using input-output tables, we find that the level and trade of change of VS trade vary substantially among these countries, and across sectors. But there are some common features overall VS share has been high in each of Lebanon and Jordan compared to those in Egypt and Turkey. The increase in VS share, which has been growing over time in each of the four countries, has mostly been driven by the manufacturing sector, specifically in high – technology products. Involvement of these countries in VS trade has been reflected on the high role of VS in explaining trade growth, especially in Lebanon and Jordan. Policy implications are finally discussed.